Inorganic sand fluidity test method, sand core structure and sand core mold for fluidity test

By designing a fluidity testing method for inorganic sand, by detecting the filling degree of sand core samples in the mold cavity and calculating the pass rate, the problem that the prior art cannot effectively test the fluidity of wet inorganic sand is solved, and efficient and accurate fluidity testing is achieved.

CN115479868BActive Publication Date: 2025-02-28NINGBO INSTITUTE OF TECHNOLOGY BEIHANG UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211087640.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-07
Publication Date
2025-02-28
Estimated Expiration
2042-09-07

AI Technical Summary

Technical Problem

The prior art cannot effectively test and characterize the fluidity of wet inorganic sand, resulting in large errors in the test results, unstable and lack of distinction.

Method used

A method of fluidity testing inorganic sand is designed to characterize fluidity by preparing sand core samples with a specific sand core structure, detecting its filling degree relative to the mold cavity, and calculating the pass rate. The method includes preparing a sand core sample, detecting the deviation between the actual weight and the standard weight, calculating the pass rate, and characterizing the fluidity by the pass rate.

Benefits of technology

It realizes simple, accurate, stable and rapid testing of the fluidity of inorganic sand, and can effectively identify the fluidity indicators of different inorganic sands, improving the quality and production efficiency of casting products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present application relates to the field of metal casting technology, and specifically to a method for testing the fluidity of inorganic sand for green casting, and accordingly provides a sand core structure and a sand core mold that match the method. Aiming at the fluidity characteristics of inorganic sand, the present application designs a slender, curved sand core structure that can correspond to the actual working conditions, and designs a corresponding sand core mold and a method for testing the fluidity of inorganic sand to match the sand core structure. The method prepares a number of sand core samples with specific structures, and assesses the degree of filling of the mold cavity by the sand core samples to evaluate whether the sand core samples are qualified, calculates the pass rate based on this, and then characterizes the fluidity index of the inorganic sand based on the pass rate. The present application can accurately, stably and quickly detect and characterize the fluidity index of inorganic sand, solving the problem that the fluidity of inorganic sand cannot be characterized in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal casting, and in particular to an inorganic sand fluidity testing method, a sand core structure for fluidity testing, and a sand core mold. Background Art

[0002] With the national energy conservation, emission reduction and green manufacturing development requirements, the foundry industry is moving towards green casting. When forming metal castings with hollow structures, it is often necessary to use casting with sand cores. The forming sand cores generally use coated sand materials, but a large amount of organic resin binders are used in traditional coated sand cores, which will produce a large amount of toxic gases such as benzene, aldehydes, and sulfur, which not only pollute the environment but also poison the human body. In recent years, new inorganic binder sands have begun to be developed and tried to be applied in the foundry industry. This inorganic sand uses modified water glass and inorganic powder additives as binders, and is currently the casting material most likely to achieve green casting production requirements.

[0003] Fluidity is one of the key performance indicators for evaluating the quality of inorganic sand. Good fluidity enables it to fully fill the mold during core shooting and core making, thereby improving the compactness and strength of the sand core, facilitating the demoulding, transportation, and core assembly of the sand core, reducing the occurrence of casting defects, and thus improving the quality and production efficiency of castings. Compared with traditional dry coated sand, casting inorganic sand is often less fluid due to its wet state, and is prone to sticking to the wall and failing to completely fill the mold.

[0004] Currently, there is no method specifically for testing the fluidity of inorganic sand. Some researchers have adopted the method of measuring the fluidity of coated sand, namely the standard flow cup method, to characterize the fluidity of inorganic sand. The principle is to characterize the fluidity of sand by measuring the time it takes for dry sand particles to flow out of the flow cup under gravity. However, the shooting process of inorganic sand is to add the mixed wet inorganic sand into the sand hopper of the core shooter, and then use compressed air to shoot the inorganic sand into the cavity of the sand core mold. Therefore, the standard flow cup method suitable for measuring dry sand particles is difficult to actually measure the fluidity of wet inorganic sand. There are many problems such as large errors in test results, instability, and lack of discrimination. Therefore, the fluidity index of inorganic sand with high humidity cannot be effectively identified.

[0005] Therefore, it is urgent to design a method and device that can accurately, stably and quickly test the fluidity of inorganic sand. Summary of the invention

[0006] The first technical problem to be solved by the present application is to provide a method for testing the fluidity of inorganic sand in view of the current status of the above-mentioned prior art, which can test and characterize the fluidity of inorganic sand simply, accurately, stably and quickly.

[0007] The second technical problem to be solved by the present application is to provide a sand core structure that matches the above-mentioned inorganic sand fluidity test method, and to reflect the structural characteristics of the actual workpiece through the designed complex sand core structure, and to assess the fluidity of the inorganic sand based on it.

[0008] The third technical problem to be solved by the present application is to provide a sand core mold that matches the above-mentioned inorganic sand fluidity test method to improve the efficiency of the inorganic sand fluidity test.

[0009] The technical solution adopted by this application to solve the above technical problems is:

[0010] In a first aspect, the present application provides a method for testing the fluidity of inorganic sand, comprising the following steps:

[0011] S10 Preparation of sand core samples: using a sand core mold to prepare inorganic sand into T sand core samples with a specific sand core structure, where T ≥ 1;

[0012] S20 Evaluation of fluidity of inorganic sand: The fluidity of the inorganic sand is evaluated by detecting the filling degree of each sand core sample prepared in S10 relative to the sand core mold cavity.

[0013] Furthermore, the evaluation of the fluidity of the inorganic sand in S20 specifically includes the following steps:

[0014] S21 detects the actual weight of each sand core sample obtained in S10, and calculates the deviation between the actual weight and the standard weight: if the deviation is less than or equal to the set threshold, it is counted as a qualified sand core sample; if the deviation is greater than the set threshold, it is counted as an unqualified sand core sample;

[0015] S22 calculates the qualified rate: qualified rate = number of qualified sand core samples / T;

[0016] S23 characterizes the fluidity of the inorganic sand by the size of the qualified rate. The higher the qualified rate, the better the fluidity.

[0017] The calculation method of the standard weight in S21 is: m 标 =V 砂芯 *ρ 无机砂 ;

[0018] In the formula, m 标 Represents standard weight; V 砂芯 Represents the theoretical volume of the designed sand core structure; ρ 无机砂 Represents the density of the inorganic sand.

[0019] In order to improve the test accuracy, the number of sand core samples prepared in the test method is T≥10; more preferably, T≥15.

[0020] It should be noted that the specific sand core structure of the sand core sample described in S10 above can be designed into a complex shape suitable for characterizing the structural characteristics of the actual workpiece according to the characteristics of the actual working conditions.

[0021] In a second aspect, the present application provides a sand core structure for testing the fluidity of inorganic sand, which is used in the fluidity testing method of the first aspect above. The sand core sample has a specific sand core structure that is an overall slender curved structure, including at least N connected curved sand samples and at least M long straight sand samples, wherein N≥1 and M≥2.

[0022] The sand core structure is designed into a complex shape consisting of multiple curved sections and multiple long straight sections, so that it is closer to the structural characteristics of actual working conditions. Its complex structural characteristics are used to assess the filling capacity of the inorganic sand, and the fluidity of the inorganic sand is further characterized based on the filling capacity of the inorganic sand.

[0023] Furthermore, the sand core structure includes a first side surface and a second side surface arranged opposite to each other, wherein the first side surface is a plane structure and the second side surface is a curved surface structure. The first side surface is designed as a plane to increase the contact area between the sand core and the mold, increase the curing speed, and enable the sand core to be cured and formed quickly; the second side surface is designed as a curved surface to facilitate demoulding.

[0024] Furthermore, the curved section sand sample is in an arc shape or a U shape, and the central angle of the curved section sand sample is 90° to 180°.

[0025] Furthermore, the length of the straight section sand sample can be set between 150 mm and 350 mm, the width of the straight section sand sample can be set between 10 mm and 50 mm, and the straight section length: effective width of the curved section can be set between 2:1 and 10:1.

[0026] Furthermore, the sand core structure may include three "1"-shaped long straight sand samples and two "U"-shaped curved sand samples, and the long straight sand samples and the curved sand samples are alternately connected to form a whole.

[0027] In a third aspect, the present application provides a sand core mold for preparing the sand core sample described in the first aspect above, the sand core mold comprising: a first mold body and a second mold body, wherein the first mold body and the second mold body are molded together to form a cavity matching the shape of the sand core structure; wherein at least one blowing hole is arranged on the surface of the first mold body, and a blowing groove connected to the blowing hole is arranged in the first mold body, and a plurality of blowing holes connected to the cavity are opened on the blowing groove; and the second mold body is provided with a sand shooting hole connected to the cavity.

[0028] Furthermore, in order to prevent the air outlet of the air blowing eye from blowing away the incompletely solidified sand core, a rectifying structure is provided at the outlet of the air blowing eye.

[0029] Furthermore, the outlet air temperature of the air blowing eye is 80-140° C., and the outlet air velocity is 50-220 m / s.

[0030] Furthermore, a plurality of air blowing holes may be arranged at intervals along the length direction of the sand core sample to more efficiently achieve heating and curing of the sand core, thereby further improving the test efficiency.

[0031] Furthermore, in accordance with the size of the sand core structure of the second aspect, the spacing between two adjacent air blowing holes can be set between 40 and 80 mm.

[0032] The beneficial effects of this application are:

[0033] 1. This application aims to solve the problem that the standard flow cup method for traditional coated sand has low precision, large test result errors, instability, lack of differentiation, and cannot effectively characterize the fluidity of inorganic sand with high humidity. A set of inorganic sand fluidity test methods is designed to evaluate whether the sand core samples are qualified by assessing the filling degree of each mold sand core sample, and the qualified rate is calculated based on this. The higher the qualified rate, the better the fluidity of the inorganic sand. The fluidity of the inorganic sand can be simply, quickly, stably and accurately characterized;

[0034] 2. This application designs a slender, curved and complex-shaped sand core structure that is close to actual working conditions in view of the characteristics of casting complex-shaped aluminum alloy workpieces and the fluidity characteristics of inorganic sand, and examines the fluidity of inorganic sand based on the sand core structure;

[0035] 3. This application also designs a sand core mold that matches the complex-shaped sand core structure and can be quickly tested. In addition to using traditional mold electric heating to cure the sand core, a hot air channel is also designed to make the sand core have a higher curing efficiency, which can greatly shorten the inorganic sand fluidity test time and improve the test efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1-Figure 2 According to some embodiments of the present application, schematic diagrams of the structure of the sand core structure in different directions are shown;

[0037] Figure 3 According to some embodiments of the present application, a schematic structural diagram of a sand core mold is shown;

[0038] Figure 4 According to some embodiments of the present application, a schematic structural diagram of a first mold body in a sand core mold is shown;

[0039] Figure 5 According to some embodiments of the present application, a partial cross-sectional view of a first mold body is shown;

[0040] Figure 6According to some embodiments of the present application, a schematic structural diagram of another implementation of the first mold body is shown;

[0041] Figure 7 According to some embodiments of the present application, a schematic structural diagram of a second mold body is shown;

[0042] Figure 8-Figure 9 According to some embodiments of the present application, a schematic structural diagram of a sand core mold and a sand core is shown;

[0043] Fig.10 According to some embodiments of the present application, a schematic diagram of the installation structure of a sand core mold is shown;

[0044] Fig.11 for Fig.10 Exploded view of;

[0045] Fig.12 This is a flow chart of the inorganic sand fluidity testing method in an embodiment of the present application. DETAILED DESCRIPTION

[0046] The following is a more detailed description of the technical features and advantages of the present application in conjunction with the accompanying drawings, so that the advantages and features of the present application can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0047] It should be noted that, in the description of the present application, terms such as "up", "down", "left", "right", "inside", and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it should not be understood as a limitation on the present invention.

[0048] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the importance of the technical features shown.

[0049] In addition, it should be noted that in the description of this application, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0050] The present application provides a method for testing the fluidity of inorganic sand, which fills the gap in the prior art in the lack of testing methods and characterization indicators for the fluidity of inorganic sand. Figure 1, is a flow chart of the liquidity testing method of this embodiment, which specifically includes the following steps:

[0051] S10 uses a sand core mold to prepare T sand core samples with a specific sand core structure from inorganic sand;

[0052] S20 evaluates the fluidity of the inorganic sand based on the T sand core samples prepared, specifically including:

[0053] S21 respectively detects the actual weight of each sand core sample prepared in S10, and calculates the deviation between the actual weight and the standard weight: if the deviation value is less than or equal to the set threshold value, it is counted as a qualified sample; if the deviation value is greater than the set threshold value, it is counted as an unqualified sample;

[0054] S22 calculates the qualified rate: qualified rate = number of qualified samples / T;

[0055] S23 characterizes the fluidity of the inorganic sand by the size of the qualified rate.

[0056] Among them, the calculation method of the standard weight of the sand core sample is: m 标 =V 砂芯 *ρ 无机砂 ;

[0057] In the formula, m 标 Represents standard weight; V 砂芯 Represents the theoretical volume of the designed sand core structure; ρ 无机砂 Represents the density of the inorganic sand.

[0058] See also Figure 2-Figure 3 , is a schematic diagram of a specific sand core structure in the inorganic sand fluidity test method of this embodiment. The sand core structure 100 is an overall slender curved structure, including three "1"-shaped straight section sand samples 120 and two "U"-shaped curved section sand samples 110. The straight section sand samples 120 and the curved section sand samples 120 are alternately connected to form a whole. The shape of the sand core structure 100 includes both curved sections and straight sections, and is a slender structure, which is close to the structural characteristics of thin-walled and complex structure aluminum alloy motor housings and other parts used for casting in actual production. The complex shape characteristics of the sand core structure 100 are used to assess the filling ability of the inorganic sand, and the fluidity of the inorganic sand is further characterized based on the filling ability.

[0059] If the sand core structure is designed into a simple L-shape or a rectangular shape, when studying the fluidity of inorganic sand, due to the simple structure of the sand core, almost all different types of inorganic sand can be packed tightly during sand shooting, but it is greatly affected by the height of the sand grains in the sand shooting tube. When the height of the sand grains is higher, the more obvious the obstruction of the sand grains to the gas is, resulting in a greater loss of kinetic energy of the gas, which reduces the initial speed of the sand grains from the sand shooting hole into the core box, and the subsequent flow and filling capacity of the sand grains are also weakened. Therefore, it is impossible to directly prove the quality of the fluidity of inorganic sand. The sand core structure 100 in the present invention is a curved and slender structure as a whole, which deliberately increases the complexity of the sand core structure and increases the resistance during the flow of inorganic sand. When shooting sand, after the sand particles reach the bottom of the core box, they accumulate into a small sand pile. The sand particles on the surface of the sand pile flow to form two jets that expand to the left and right walls of the core box respectively. The sand particles at the bottom of the sand pile are compacted, and their particle volume fraction is larger than that on the surface of the sand pile and is close to the maximum value. The experimental results are more consistent with the flow front morphology of inorganic sand. The experimental results can provide scientific guidance for the determination of process plans and the optimization of mold structures in actual production. At the same time, the entire sand core structure is not overly complex, avoiding the problem that the sand core mold is difficult to process, inconvenient to disassemble and clean.

[0060] Furthermore, the sand core structure 100 includes a first side surface 130 and a second side surface 140 that are arranged relatively to each other, wherein the first side surface 130 is a planar structure, which is convenient for increasing the contact area between the sand core and the mold, and can increase the heating speed of the mold to the sand core, thereby improving the curing molding speed; the second side surface 140 is a curved surface structure, which is convenient for ejecting the sand core out of the mold cavity for demolding.

[0061] See also Figure 4-Figure 12 , is a structural schematic diagram of a sand core mold used in the inorganic sand fluidity test method of this embodiment. The sand core mold 200 is used to prepare a sand core sample with a specific sand core structure, and each sand core sample has the shape of the sand core structure 100 described above. The sand core mold 200 includes: a first mold body 210 and a second mold body 220. After the first mold body 210 and the second mold body 220 are molded together, a cavity matching the shape of the sand core structure 100 is formed; wherein, a blowing hole 211 is arranged above the first mold body 210, and a connected blowing groove 212 is arranged below the blowing hole 211. A plurality of blowing holes 213 are opened on the blowing groove 212, and the blowing holes 213 are connected to the cavity; hot air is introduced into the blowing hole 211, and the hot air is then blown into the cavity through the blowing groove 212 and the blowing hole 213, which is used to blow and heat the sand core sample in the cavity, thereby increasing the curing speed of the sand core sample and shortening its curing time, thereby improving the efficiency of the fluidity test.

[0062] The number of the blowing holes 211 can be set to one or more. Figure 5-Figure 6, is a structural schematic diagram of the first mold body 210 in this embodiment. The number of blowing holes 211 is set to three. Correspondingly, three blowing grooves 212 are opened inside the first mold body 210. The three blowing grooves 212 correspond to the three straight sections of the sand samples 120 of the sand core structure 100, and each blowing groove 212 is arranged with a plurality of blowing eyes 213 at intervals. Hot air is introduced from the three blowing holes 211 respectively, and passes through the blowing grooves 212 to each blowing eye 213, and is blown from the blowing eye 213 to the sand core sample for heating, thereby improving its curing rate.

[0063] See also Figure 7 , is a structural schematic diagram of another implementation manner of the first mold body 210 in this embodiment. Only one blowing hole 211 needs to be set on the first mold body 210. Correspondingly, only one blowing groove 212 is opened inside the first mold body 210. At least one blowing eye (not shown in the figure) is arranged on the blowing groove 212. After the hot air enters through the blowing hole 211, it is blown into the mold cavity through the blowing eye and then circulates along the mold cavity to heat the sand core sample. Although only one blowing hole 211 and the blowing groove 212 are set, the heating efficiency of the hot air is slightly reduced, but the structure and processing difficulty of the first mold body 210 are simplified.

[0064] It should be noted that the air blowing groove 212 is designed as a straight groove structure in order to reduce the difficulty of processing. In some other embodiments, the air blowing groove 212 can also be designed as a curved channel structure that matches the curved shape of the sand core structure 100. Multiple air holes are arranged on the air blowing groove 212 at intervals along the length direction of the sand core sample, which can further improve the heating effect.

[0065] In some preferred embodiments, a rectifying structure (not shown) is further provided at the outlet of the air blowing hole 213 to prevent hot air from blowing directly toward the sand core sample and blowing away the uncured sand core. For example, the rectifying structure may be an exhaust plug.

[0066] See also Figure 5-Figure 7 The first mold body 210 includes a first cavity side wall 214 that matches the first side surface 130 of the sand core structure 100. A plurality of air blowing holes 213 are provided on the first cavity side wall 214. The first side surface 130 of the sand core structure 100 is designed as a plane structure, which can increase the contact area between the sand core sample and the mold, improve the heating efficiency of the mold to the sand core sample, and increase the curing speed so that the sand core sample can be quickly cured and formed.

[0067] See also Figure 8, is a schematic diagram of the structure of the second mold body 220 in this embodiment. A sand-shooting hole 221 is arranged on the upper side of the second mold body 220 for connecting to a sand-shooting machine to shoot sand into the mold cavity. The second mold body 220 also includes a second mold cavity side wall 222 that matches the second side surface of the sand core structure 100. The second side surface 140 of the sand core structure 100 is designed as a curved surface structure to facilitate ejection of the sand core sample. A plurality of ejector holes 223 are provided on the second mold cavity side wall 222 for connecting to an ejector to eject the sand core sample out of the mold cavity.

[0068] See also Figure 9-10 , is a schematic diagram of the matching structure of the sand core mold 200 and the sand core structure 100 in this embodiment. The first mold body 210 and the second mold body 220 are respectively provided with a first temperature measuring hole 215 and a second temperature measuring hole 224, which are used to install a temperature detection device to detect the temperature on both sides of the sand core structure 100 in real time. The temperature detection device can interlock and control the hot air source and / or the heating device of the mold to more accurately control the heating power of the sand core sample. Exemplarily, the above-mentioned temperature detection device can be a probe-type K-type thermocouple.

[0069] See also Figure 11-Figure 12 , is a schematic diagram of the installation of the sand core mold 200 in this embodiment. The first mold body 210 is closely connected to the first fixed plate 230, and the second mold body 220 is closely connected to the second fixed plate 240. The first fixed plate 230 and the second fixed plate 240 are respectively provided with a plurality of first heating tubes 251 and second heating tubes 252 for rapid heating and heat preservation of the sand core sample. That is, the sand core mold 200 of this embodiment improves the curing speed of the sand core sample by a dual heating method of heating by heating tubes on both sides and auxiliary heating by hot air, thereby improving the efficiency of the fluidity test. Among them, the first heating tube 251 and the second heating tube 252 can be dry-burning electric heating tubes, which heat the sand core sample through the first mold body 210 and the second mold body 220. Hot air at 80°C to 140°C is introduced into the air hole 211 to assist in heating the sand core sample.

[0070] The right side of the second fixed plate 240 is further connected to a movable baffle 260, on which a plurality of ejector pins 261 are fixed, and the ejector pins 261 pass through the second fixed plate 240 and the second mold body 220 to communicate with the mold cavity. Preferably, a plurality of ejector pins 261 are arranged at intervals along the length direction of the sand core sample, and are used to quickly eject the inorganic sand core sample from the mold cavity when the mold is opened, so as to further improve the test efficiency. The ejector plate 260 is connected to a power part such as a cylinder to provide power for ejecting the sand core.

[0071] The test method is specifically described below through multiple embodiments. In the embodiments, each sand core sample is prepared by the sand core mold 200, and the prepared sand core sample has a shape as shown in the sand core structure 100. In each embodiment, the other conditions not specified are carried out according to conventional conditions or conditions recommended by the manufacturer, and the reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased from the market.

[0072] The standard weight of the sand core sample is calculated by multiplying the volume of the designed sand core structure by the density of the prepared inorganic sand, and the actual weight of each prepared sand core sample is weighed by an analytical balance.

[0073] Embodiment 1:

[0074] Step 1: Preparation of powder additives for foundry inorganic sand

[0075] According to the formula, 10g of microsilica powder, 5g of 325 mesh white mica powder, 2.5g of 200-1500 mesh hollow glass microspheres, and 2.5g of 5000 mesh active magnesium oxide were weighed. 5g of microsilica powder was added to a conical double-screw mixer and stirred for 1 minute, and then 5g of white mica powder, 5g of microsilica powder, 2.5g of hollow glass microspheres, and 2.5g of active alumina were added to the conical double-screw mixer in sequence and stirred for 2 minutes each time a raw material was added; after all the above steps were completed, the machine was kept stirred for 5 minutes to obtain a powder additive for casting inorganic sand.

[0076] Step 2: Weigh

[0077] Weigh 50 g of industrial liquid sodium silicate with a modulus of 2.3 and a solid content of 38.5%, 15 g of powder additive for foundry inorganic sand, and 2.5 kg of Dalin scrubbing silica sand with a particle size of 50 / 100 mesh, and pour them into containers respectively for use.

[0078] Step 3: Sand Mixing

[0079] According to the formula, first mix 15g of modified powder with 2.5kg of 50 / 100 mesh Dalin scrubbing silica sand in a sand mixer for 0.5 to 3 minutes. After mixing evenly, the resulting mixture is evenly mixed with 50g of liquid sodium silicate and continues to mix for 0.5 to 3 minutes. After evenly mixing, the sand can be produced.

[0080] Step 4: Prepare the inorganic sand core sample

[0081] Add the mixed inorganic mortar into the sand bucket of the core shooter, and preheat the sand core mold 200 to 200°C. Use compressed air to shoot the inorganic sand composition into the mold cavity of the sand core mold 200 using an inorganic core shooter at a pressure of 0.3Mpa, and then blow 180°C hot air into the mold cavity through the blowing hole, with a blowing pressure of 0.3Mpa and a blowing time of 60s. After the sand core hardens, open the box and eject the sand core. The sand core can be used on the same day or stored for more than 3 days. Repeat step 4 to obtain 10 sand core samples.

[0082] Embodiment 2:

[0083] Step 1: Preparation of powder additives for foundry inorganic sand

[0084] According to the formula, 10g of microsilica powder, 5g of 325 mesh sericite powder, and 2.5g of 5000 mesh active magnesium oxide were weighed. 5g of microsilica powder was added to a conical double-screw mixer and stirred for 1 minute, and then 5g of sericite powder, 5g of microsilica powder, and 2.5g of active magnesium oxide were added to the conical double-screw mixer in sequence and stirred for 2 minutes each time a raw material was added; after all the above steps were completed, the machine was kept stirred for 5 minutes to obtain a powder additive for casting inorganic sand.

[0085] Step 2: Weigh

[0086] Weigh 50 g of industrial liquid sodium silicate with a modulus of 2.3 and a solid content of 38.5%, 15 g of powder additive for foundry inorganic sand, and 2.5 kg of Dalin scrubbing silica sand with a particle size of 50 / 100 mesh, and pour them into containers respectively for use.

[0087] Step 3: Sand Mixing

[0088] According to the formula, first mix 15g of modified powder with 2.5kg of 50 / 100 mesh Dalin scrubbing silica sand in a sand mixer for 0.5 to 3 minutes. After mixing evenly, the resulting mixture is evenly mixed with 50g of liquid sodium silicate and continues to mix for 0.5 to 3 minutes. After evenly mixing, the sand can be produced.

[0089] Step 4: Prepare the inorganic sand core sample

[0090] Add the mixed inorganic mortar into the sand bucket of the core shooter, and preheat the sand core mold 200 to 200°C. Use compressed air to shoot the inorganic sand composition into the cavity of the sand core mold 200 with the inorganic core shooter at a pressure of 0.3Mpa, and then blow 180°C hot air into the cavity, with a blowing pressure of 0.3Mpa and a blowing time of 60s. After the sand core is hardened, open the box and eject the sand core. The sand core can be used on the same day or stored for more than 3 days. Repeat step 4 to obtain 10 sand core samples.

[0091] Embodiment 3:

[0092] Step 1: Preparation of powder additives for foundry inorganic sand

[0093] According to the formula, 10g of microsilica powder, 5g of 100-mesh white mica powder, 2.5g of 200-1500-mesh hollow glass microspheres, and 2.5g of 5000-mesh activated alumina are weighed. 5g of microsilica powder is added to a conical double-screw mixer and stirred and dispersed for 1 minute, and then 5g of white mica powder, 5g of microsilica powder, 2.5g of hollow glass microspheres, and 2.5g of activated magnesium oxide are added to the conical double-screw mixer in sequence and stirred and dispersed. Each time a raw material is added, the machine should be turned on and stirred for 2 minutes; after all the above steps are completed, the machine should be turned on and stirred for 5 minutes to obtain a powder additive for casting inorganic sand.

[0094] Step 2: Weigh

[0095] Weigh 50 g of industrial liquid sodium silicate with a modulus of 2.3 and a solid content of 41%, 15 g of powder additive for foundry inorganic sand, and 2.5 kg of Dalin scrubbing silica sand with a particle size of 50 / 100 mesh, and pour them into containers respectively for use.

[0096] Step 3: Sand Mixing

[0097] According to the formula, first mix 15g of modified powder with 2.5kg of 50 / 100 mesh Dalin scrubbing silica sand in a sand mixer for 0.5 to 3 minutes. After mixing evenly, the resulting mixture is evenly mixed with 50g of liquid sodium silicate and continues to mix for 0.5 to 3 minutes. After evenly mixing, the sand can be produced.

[0098] Step 4: Prepare the inorganic sand core sample

[0099] Add the mixed inorganic mortar into the sand bucket of the core shooter, and preheat the sand core mold 200 to 200°C. Use compressed air to shoot the inorganic sand composition into the cavity of the sand core mold 200 with the inorganic core shooter at a pressure of 0.3Mpa, and then blow 180°C hot air into the cavity, with a blowing pressure of 0.3Mpa and a blowing time of 60s. After the sand core is hardened, open the box and eject the sand core. The sand core can be used on the same day or stored for more than 3 days. Repeat step 4 to obtain 10 sand core samples.

[0100] Embodiment 4:

[0101] Step 1: Preparation of powder additives for foundry inorganic sand

[0102] According to the formula, 10g of microsilica powder, 5g of 300-mesh graphite, and 2.5g of 5000-mesh active magnesium oxide were weighed. 5g of microsilica powder was added to a conical double-screw mixer and stirred for 1 minute, and then 5g of graphite, 5g of microsilica powder, and 2.5g of active magnesium oxide were added to the conical double-screw mixer in sequence and stirred for 2 minutes each time a raw material was added; after all the above steps were completed, the machine was kept stirred for 5 minutes to obtain a powder additive for casting inorganic sand.

[0103] Step 2: Weigh

[0104] Weigh 50 g of industrial liquid sodium silicate with a modulus of 2.3 and a solid content of 41%, 15 g of powder additive for foundry inorganic sand, and 2.5 kg of Dalin scrubbing silica sand with a particle size of 50 / 100 mesh, and pour them into containers respectively for use.

[0105] Step 3: Sand Mixing

[0106] According to the formula, first mix 15g of modified powder with 2.5kg of 50 / 100 mesh Dalin scrubbing silica sand in a sand mixer for 0.5 to 3 minutes. After mixing evenly, the resulting mixture is evenly mixed with 50g of liquid sodium silicate and continues to mix for 0.5 to 3 minutes. After evenly mixing, the sand can be produced.

[0107] Step 4: Prepare the inorganic sand core sample

[0108] Add the mixed inorganic mortar into the sand hopper of the core shooting machine, and preheat the sand core mold 200 to 200°C. Use compressed air to shoot the inorganic sand composition into the mold cavity of the sand core mold 200 at a pressure of 0.3Mpa, and then blow 180°C hot air into the mold cavity, with a blowing pressure of 0.3Mpa and a blowing time of 60s. After the sand core hardens, open the box and eject the sand core. The sand core can be used on the same day or stored for more than 3 days. Repeat step 4 to obtain 10 sand core samples.

[0109] Embodiment 5:

[0110] Step 1: Preparation of powder additives for foundry inorganic sand

[0111] According to the formula, 10g of microsilica powder, 5g of 100-mesh white mica powder, 2.5g of 200-1500-mesh hollow glass microspheres, and 2.5g of 5000-mesh active magnesium oxide were weighed. 5g of microsilica powder was added to a conical double-screw mixer and stirred for 1 minute, and then 5g of white mica powder, 5g of microsilica powder, 2.5g of hollow glass microspheres, and 2.5g of active magnesium oxide were added to the conical double-screw mixer in sequence and stirred for 2 minutes each time a raw material was added; after all the above steps were completed, the machine was kept stirred for 5 minutes to obtain a powder additive for casting inorganic sand.

[0112] Step 2: Weigh

[0113] Weigh 50 g of industrial liquid sodium silicate with a modulus of 2.3 and a solid content of 46.5%, 15 g of powder additive for foundry inorganic sand, and 2.5 kg of Dalin scrubbing silica sand with a particle size of 50 / 100 mesh, and pour them into containers respectively for use.

[0114] Step 3: Sand Mixing

[0115] According to the formula, first mix 15g of modified powder with 2.5kg of 50 / 100 mesh Dalin scrubbing silica sand in a sand mixer for 0.5 to 3 minutes. After mixing evenly, the resulting mixture is evenly mixed with 50g of liquid sodium silicate and continues to mix for 0.5 to 3 minutes. After evenly mixing, the sand can be produced.

[0116] Step 4: Prepare the inorganic sand core sample

[0117] Add the mixed inorganic mortar into the sand hopper of the core shooter, and preheat the sand core mold 200 to 200°C. Under 0.3Mpa air pressure, use compressed air to shoot the inorganic sand composition into the mold cavity with the inorganic core shooter, and then blow 180°C hot air into the cavity, with a blowing pressure of 0.3Mpa and a blowing time of 60s. After the sand core hardens, open the box and eject the sand core. The sand core can be used on the same day or stored for more than 3 days. Repeat step 4 to obtain 10 sand core samples.

[0118] Embodiment 6:

[0119] Step 1: Preparation of powder additives for foundry inorganic sand

[0120] According to the formula, 10g of microsilica powder, 5g of 300-mesh graphite, and 2.5g of 5000-mesh active magnesium oxide were weighed. 5g of microsilica powder was added to a conical double-screw mixer and stirred for 1 minute, and then 5g of graphite, 5g of microsilica powder, and 2.5g of active magnesium oxide were added to the conical double-screw mixer in sequence and stirred for 2 minutes each time a raw material was added; after all the above steps were completed, the machine was kept stirred for 5 minutes to obtain a powder additive for casting inorganic sand.

[0121] Step 2: Weigh

[0122] Weigh 50 g of industrial liquid sodium silicate with a modulus of 2.3 and a solid content of 46.5%, 15 g of powder additive for foundry inorganic sand, and 2.5 kg of Dalin scrubbing silica sand with a particle size of 50 / 100 mesh, and pour them into containers respectively for use.

[0123] Step 3: Sand Mixing

[0124] According to the formula, first mix 15g of modified powder with 2.5kg of 50 / 100 mesh Dalin scrubbing silica sand in a sand mixer for 0.5 to 3 minutes. After mixing evenly, the resulting mixture is evenly mixed with 50g of liquid sodium silicate and continues to mix for 0.5 to 3 minutes. After evenly mixing, the sand can be produced.

[0125] Step 4: Prepare the inorganic sand core sample

[0126] Add the mixed inorganic mortar into the sand hopper of the core shooting machine, and preheat the sand core mold 200 to 200°C. Use compressed air to shoot the inorganic sand composition into the mold cavity at a pressure of 0.3Mpa, and then blow 180°C hot air into the cavity, with a blowing pressure of 0.3Mpa and a blowing time of 60s. After the sand core hardens, open the box and eject the sand core. The sand core can be used on the same day or stored for more than 3 days. Repeat step 4 to obtain 10 sand core samples.

[0127] The standard weight of the sand core made of inorganic sand with different compositions in each embodiment was calculated, and the actual weight of the sand core sample made in each embodiment was weighed; wherein, in each embodiment, an inorganic binder sand mixture was prepared by using powder additives for casting inorganic sand and a binder in different proportions, and after weighing the sand core sample made in each embodiment, the specific performance data are shown in Table 1.

[0128] Table 1 Weight data of sand core samples prepared in each embodiment

[0129]

[0130] In each embodiment, since each sand core sample is made of the same sand core mold and has the same sand core structure, the theoretical volume of each sand core sample is the same, and the theoretical volume can be calculated according to the volume of the designed sand core structure 100; however, since the density of the inorganic sand mixture obtained by mixing powder additives with different components and particle size distribution and water glass with different modulus is different, the standard weight of the sand core sample in each embodiment is different. As shown in Table 1, compared with Embodiments 1, 3, and 5 and Embodiments 2, 4, and 6, the difference is that the bulk sodium silicate used is the same, and a certain amount of hollow glass microspheres are used in the modified powder used in Embodiments 1, 3, and 5 to replace microsilica powder. Hollow glass microspheres are a tiny, hollow spherical powder with a smaller density than microsilica powder. Therefore, the density of the inorganic sand mixture obtained in Embodiments 1, 3, and 5 is lower than that in Embodiments 2, 4, and 6, respectively. Compared with Embodiments 1, 2, and 3, the difference is that the modified powder used is the same, but the solid content of the liquid sodium silicate is different, and the inorganic sand mixture with a high solid content has a slightly higher sand density. Therefore, the standard masses of the sand core samples in Examples 1-6 are different. The sand shooting process of the inorganic sand mixture is essentially a particle flow, that is, the inorganic sand particles gathered in the sand shooting tube are subjected to the pressure of the high-pressure gas and the internal force between the particles, and a filling and compacting process similar to a fluid occurs in the mold (core) box. When inorganic sands of different densities, viscosities, and states are sand shot using the sand core mold of the present invention, the stacking densities in the same sand core mold cavity are different, and the particles with a larger volume fraction have a larger sand core weight.

[0131] The deviation between the actual weight and the standard weight of the sand core sample in each embodiment was calculated to obtain the experimental data shown in Table 2.

[0132] Table 2 Deviation data of actual weight and standard weight of sand core samples in each embodiment

[0133]

[0134] In the embodiment, the deviation threshold between the weight of the qualified sand core sample and the standard weight is set to 3%, and the deviation value is compared with the set threshold (3%). If the deviation is less than the set threshold, it is counted as a qualified sand core sample; if the deviation is greater than the set threshold, it is counted as an unqualified sand core sample. The number of qualified samples, the number of unqualified samples and the total number of samples of the sand cores made of inorganic sands of different components in each embodiment are counted, and the qualified rate is calculated. The higher the qualified rate, the better the fluidity of the inorganic sand, and the experimental data shown in Table 3 are obtained. As shown in Table 3, combined with the test results and actual experience of the inventor, the qualified rate of Example 3 is 100%, and the fluidity of the inorganic sand used is "good"; the qualified rate of Examples 1, 4, and 5 is 90%, and the fluidity of the inorganic sand used is "average"; the qualified rate of Example 2 is 80%, and the fluidity of the inorganic sand used is "poor"; the qualified rate of Example 6 is only 70%, and the fluidity of the inorganic sand used is "very poor".

[0135] Table 3 Inorganic sand fluidity index of each embodiment

[0136]

[0137] As can be seen from Table 3, the fluidity of Examples 1, 3, and 5 using hollow glass microspheres is better than that of Examples 2, 4, and 6 not using hollow glass microspheres. From the perspective of material mechanism, this is because hollow glass microspheres are a type of spherical silicate with good dispersibility, fluidity, and stability. When hollow glass microspheres are applied to inorganic sand mixtures, they can be directly filled in silica sand grains and other powder additives. The effect of spherical silicates is to add ultrafine round spherical flow aid ultrafine powder to the inorganic sand mixture, so that it is evenly distributed on the rough and uneven surface of the sand grains, isolating the direct contact of the surface of the sand grains. The movement of the sand grains is achieved by the rolling of the ultrafine spheres, thereby greatly reducing the active friction resistance between the sand grains and changing the original bite state between the sand grains to the bite state between the sand grains and the round flow aids and the bite state between the round flow aids, which greatly reduces the bite friction resistance of the molding sand system and improves the fluidity of the molding sand. This is consistent with the fluidity test results represented in Table 3.

[0138] In addition, the fluidity of the inorganic sand mixture obtained by using different solid contents of liquid sodium silicate is also different. As can be seen from Table 3, the fluidity of Example 3 is better than that of Examples 1 and 5. This is because liquid sodium silicate is a system in which true solution (ion and molecular dispersion) and colloidal solution (colloidal dispersion) of sodium silicate coexist in water. The lower the solid content, the greater the proportion of true solution; the higher the solid content, the greater the proportion of colloidal solution, and the easier it is to solidify due to gelation. When the sodium silicate solution approaches the gelation point, most of the true solution disappears and is basically in the state of colloidal solution, which is at the critical value. One step forward from the critical value (i.e., the solid content increases), that is, it tends to solidify due to gelation, and its fluidity will deteriorate. When the solid content is lower than the critical value, the amount and size of the sodium silicate gel contained in the solution are relatively lower, and it often does not play the role of bonding sand particles with larger particle size, but agglomerates powder additives such as "spherical hollow glass microspheres" that can increase fluidity during the sand mixing process, reducing the fluidity of the inorganic sand mixture. Therefore, the solid content of the sodium silicate solution is most suitable near the critical value. In Example 5, the solid content of the liquid sodium silicate far exceeds the critical value, the viscosity of the sodium silicate solution increases significantly, and it is very "sticky". The obtained inorganic sand mixture should have worse fluidity than Examples 1 and 3. The solid content of Examples 1 and 3 is lower than the critical value, but the solid content of Example 3 is closer to the critical value, so the fluidity of Example 3 should be better than that of Examples 1 and 5. This is consistent with the fluidity test results represented in Table 3.

[0139] It can be seen from the above analysis results that the fluidity testing method of the present invention can accurately, stably and quickly evaluate the fluidity of different types of inorganic sand mixtures.

[0140] In the description of this specification, the description with reference to the terms "some embodiments", "some examples", "exemplarily", "example", "preferably", or "further" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0141] The above descriptions are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for testing the fluidity of inorganic sand, characterized in that: The following steps are involved: S10 preparing sand core samples: using a sand core mold to prepare inorganic sand into T sand core samples, where T ≥ 10; S20 Inorganic Sand Fluidity Evaluation: S21 detects the actual weight of each sand core sample obtained in S10, and calculates the deviation between the actual weight and the standard weight: if the deviation is less than or equal to the set threshold, it is counted as a qualified sand core sample; if the deviation is greater than the set threshold, it is counted as an unqualified sand core sample; S22 Calculate the qualified rate: qualified rate = number of qualified sand core samples / T; S23 The qualified rate is used to characterize the fluidity of the inorganic sand. The higher the qualified rate, the better the fluidity. The calculation method of the standard weight in S21 is: m 标 =V 砂芯 *ρ 无机砂 ; In the formula, m 标 Represents standard weight; V 砂芯 Represents the theoretical volume of the designed sand core structure; ρ 无机砂 Represents the density of the inorganic sand; In step S10, the structure of the sand core sample is an overall slender curved structure, including at least N connected curved section sand samples and at least M long straight section sand samples, wherein N≥1, M≥2; the structure of the sand core sample includes a first side surface and a second side surface arranged relatively to each other, wherein the first side surface is a plane structure and the second side surface is a curved surface structure; the curved section sand sample is arc-shaped or U-shaped, and the central angle corresponding to the curved section sand sample is 90° to 180°.

2. The inorganic sand fluidity testing method according to claim 1, characterized in that: In step S10, the structure of the sand core sample includes three "1"-shaped long straight sand samples and two "U"-shaped curved sand samples, and the long straight sand samples and the curved sand samples are alternately connected to form a whole.

3. A sand core mold, used in the fluidity testing method according to any one of claims 1 to 2, characterized in that: include: A first mold body and a second mold body, wherein the first mold body and the second mold body are molded together to form a mold cavity matching the structural shape of the sand core sample; Wherein, at least one blowing hole is arranged on the surface of the first mold body, a blowing groove connected with the blowing hole is arranged in the first mold body, and a plurality of blowing holes connected with the mold cavity are opened on the blowing groove; and a sand-shooting hole connected with the mold cavity is arranged on the surface of the second mold body.

4. The sand core mold according to claim 3, characterized in that: A rectifying structure is arranged at the outlet of the air blowing eye.

5. The sand core mold according to claim 4, characterized in that: The outlet air temperature of the air blowing eye is 80-140° C., and the outlet air velocity is 50-220 m / s.

Citation Information

Patent Citations

  • Intake sand -core mold subassembly of automatic drawing of patterns of return bend of production internal -combustion engine

    CN208408478U

  • Sand Core Making Machine and Method

    US20190275581A1